Islamic psychology and the call for Islamization of modern psychology = Psikologi Islam dan panggilan bagi pengislaman psikologi moden - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (International Islamic University Malaysia, 2012)
The shifting of paradigms in modern psychology has left modern men in a state of confusion on the issues pertaining to what should be the paramount concern of psychology and in the proper understanding on the topic of human nature. In a contrastive manner Islamic psychology which has been promoted by Muslim scholars alongside with the process of Islamization of knowledge and education, has its roots in the philosophical ideas of early Muslim scholars. Its resurgence, which started some two decades ago, is seen as an initiative to introduce Islamic understanding on man to the conflicting ideas prevalent in modern psychology. Its approach, which is mainly philosophical in nature, goes back to the ideas on man mentioned in the two primary sources of Islam, the Qur’an and ×adÊth. Islamic psychology with its comprehensive ideas on human nature has been seen by Muslim scholars as a new perspective in psychology that can fill in the lacunae present in the modern psychological thoughts on man, and clears the mist that surrounds most Western theories on man. This paper represents an attempt to analyze and also synthesize Western psychology and Islamic psychology in terms of their nature, development, contributions, and problems.